Identification of Soybean Resistance to Pod Sucking Bug (Riptortus linearis) by No-Choice Test - Ayda Krisnawati; Marida Santi Yudha Ika Bayu; Moch. Muchlish Adie (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Soybean pod damaged by pod sucking bug (Riptortus linearis) is one of the constraint within soybean yield improvement in Indonesia. The research aimed was to identify the resistance of soybean genotypes to pod sucking pest. The experiment was conducted in Iletri’s screen house from March to June 2015. The experiment was arranged in Randomized Completely Block Design using 10 soybean genotypes with three replicates. The soybean resistance was evaluated using no-choice test. Data collected on number of pod/plant, number of seed/plant, seed weight per plant, number of attacked pod/plant, and number of attacked seed/plant. The result showed that the lowest percentage both of pod and seed damage was G511H/Anjasmoro//Anjasmoro-2-8, that was 25.83 % and 19.12 %, respectively. Based on the value of the percentage of seed damage, there were five susceptible genotypes, three moderately resistant, and two resistant genotypes. Based on the value of the percentage of pod damage, showed four susceptible genotypes, five moderately resistant, and a resistant genotype. G511H/Anjasmoro//Anjasmoro-2-8 was the only resistant genotype, and it could be used as a genetic source in the improvement of soybean resistance to pod sucking bug.How to CiteKrisnawati, A., Bayu, M. S. Y. I. Adie, M. M. (2016). Identification of Soybean Resistance to Pod Sucking Bug (Riptortus linearis) by No-Choice Test. Biosaintifika: Journal of Biology Biology Education, 8(3), 407-414.